2020
DOI: 10.1001/jamanetworkopen.2020.18728
|View full text |Cite
|
Sign up to set email alerts
|

Association of Medicaid Expansion Under the Patient Protection and Affordable Care Act With Use of Long-term Care

Abstract: This cohort study uses data from the Health and Retirement Study to examine the association between Patient Protection and Affordable Care Act funded–Medicaid expansion in 2014 and long-term care use among low-income, middle-aged adults newly eligible for Medicaid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…This shift in cost from inpatient settings to outpatient settings would also be consistent with the hypothesis that Medicaid-eligible patients benefit from access to outpatient care, which may continue into their Medicare years and mitigate the risk and cost of hospitalizations for acute events. Interestingly, prior literature has suggested that Medicaid access is associated with an increase in utilization of long-term care, 34 including home health which is consistent with our findings, but also skilled nursing which was inconsistent with our findings. This could suggest that reduced Medicare spending on skilled nursing is merely an artifact of shifting the burden to Medicaid, which is an important source of skilled nursing reimbursement.…”
Section: Discussioncontrasting
confidence: 87%
“…This shift in cost from inpatient settings to outpatient settings would also be consistent with the hypothesis that Medicaid-eligible patients benefit from access to outpatient care, which may continue into their Medicare years and mitigate the risk and cost of hospitalizations for acute events. Interestingly, prior literature has suggested that Medicaid access is associated with an increase in utilization of long-term care, 34 including home health which is consistent with our findings, but also skilled nursing which was inconsistent with our findings. This could suggest that reduced Medicare spending on skilled nursing is merely an artifact of shifting the burden to Medicaid, which is an important source of skilled nursing reimbursement.…”
Section: Discussioncontrasting
confidence: 87%
“…Positive effects may result from several mechanisms such higher disposable income (e.g., by reducing out of pocket expenses), better access to health care (to address acute and chronic conditions that destabili e one s life in other domains such as work) and lower costs in the event of needing care (averting catastrophic costs). Similarly, Medicaid expansion improved the access to formal paid long-term care (Van Houtven et al, 2020). However, the effects of ACA-Medicaid expansion are specifically important among a population that otherwise has limited access to insurance because they perform caregiving duties low-income caregiving spouses.…”
Section: Medicaid Expansionmentioning
confidence: 99%
“…9 In the few studies that have examined these trends beyond the first 2 years of coverage expansion, increases in coverage, access, and affordability as well as shifts in utilization have persisted through the first 3 years of ACA implementation. 10,11 The association of coverage expansion under the ACA with quality of care remains largely unexamined, although 2 initial studies 5,12 have identified an association between Medicaid expansion and patient-reported access to and experiences with chronic care. In addition, among patients at federally funded health centers, Medicaid expansion was associated with improved quality in asthma treatment, Papanicolaou testing, body mass index assessment, and hypertension control, but not differences in other examined measures.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these findings extend to young adults and low-income and middle-income families with children . In the few studies that have examined these trends beyond the first 2 years of coverage expansion, increases in coverage, access, and affordability as well as shifts in utilization have persisted through the first 3 years of ACA implementation …”
Section: Introductionmentioning
confidence: 99%